Vodikov sulfid - signalna molekula s terapevtskim potencialom - Pavlin, Tajda (Farmacevtski vestnik, 2025)
Hydrogen sulfide, along with carbon monoxide and nitric oxide, is an important signaling molecule that is endogenously synthesized by specific enzymes. It is involved in various physiological processes, including vasodilation, neuromodulation, and neuroprotection. Its role in protecting cells from oxidative stress is significant, and research has shown that it also regulates apoptosis and cell proliferation. Additionally, hydrogen sulfide has anti-inflammatory properties, although in some contexts, it may exert pro-inflammatory effects. Despite its many beneficial actions, it is toxic at high concentrations, as it inhibits cytochrome c oxidase, disrupting the respiratory chain, promoting the formation of reactive oxygen species, and leads to cellular damage. hydrogen sulfide donors show potential for treating conditions such as myocardial ischemia, neurodegenerative diseases, and inflammatory disorders; however, their mechanisms of action and safety profiles require further investigation.
Keywords: citokrom c oksidaza; cytochrome c oxidase; hydrogen sulfide; neurodegenerative diseases; Nevrodegenerativne bolezni; vasodilation; vazodilatacija; vodikov sulfid